Using Translation to Identify Difficult English Tenses for EFL Students - Arcade Nduwimana; Fabiola Ndayiragije; Clément Ndoricimpa (Institut Agama Islam Negeri (IAIN) Manado, 2026)
Advocating the view that translation is a natural process and hence a pedagogic tool, this study was conducted to uncover challenging English tenses for EFL students by means of translation from the native language into English. To achieve this aim, researchers hypothesized that simple tenses are less difficult for students than perfect tenses and that present tenses are less difficult than past tenses. The researchers adopted a quantitative research design and randomly selected a sample of 126 students from the targeted population of 185. They were asked to translate into English a text initially written in their native language that was structured in such a way that it would include as many tenses as possible if translated. Of the 126 students, 121 completed the task appropriately, leading to a response rate of 96.03 %. The researchers analysed the collected data using SPSS version 22. The findings indicated that the most difficult tenses for students were the future perfect, present perfect continuous, past perfect continuous, and past perfect. Further analysis showed that students faced fewer difficulties in using simple tenses compared to perfect tenses and fewer difficulties in using present tenses compared to past tenses. Pedagogically, these findings imply that EFL teachers need to pay particular attention to the past and perfect English tenses especially those having no equivalents in the learners’ native language.Keywords: Translation; English tenses; time; aspect; Native language text